The role of Interleukin-4 induced gene 1 (IL-4i1) in allergic asthma and atopic dermatitis - Ngomti, Amkele (Department of Pathology, 2023)
Allergies are described as an unnecessary immune response to non-harmful substances known as allergens. Both allergic asthma and atopic dermatitis (AD) are said to be induced by elevated levels of immunoglobulin E (IgE) and T helper 2 (Th2) immune cells and inflammatory associated cells such as eosinophils, mast, and basophils. Globally, asthma is affecting more than 300 million people and is characterized by chronic airway inflammation, reversible airflow limitation, and airway hyperreactivity. AD is affecting approximately 15%-20% of the pediatric population and 7%-10% of adults in the world and is characterized by dysregulation of skin barrier and immunity, eczematous lesions, dry and itchy skin. Dysfunctional tolerogenic immune response to these innocuous allergens has been described as a leading cause of allergic disease pathogenesis. Interleukin-4 induced gene 1 (IL-4i1) is a secreted L-amino acid oxidase enzyme mainly expressed by antigen-presenting cells (APCs) and upon activation by IL-4 and CD40, can be induced in B lymphocytes. IL-4i1 converts phenylalanine into phenylpyruvate, ammonia, and hydrogen peroxide which can induce effector T cells suppression by inhibiting their activation, proliferation, and cytokine production while promoting a regulatory T cell (Tregs) arm. The contribution of IL-4i1 and its immunoregulatory potential has not yet been explored in allergic asthma and atopic dermatitis. Thus, we proposed to investigate the role of IL-4i1 during allergic asthma and atopic dermatitis using acute mouse models. Female mice of 8-12 weeks old either sufficient (IL-4i1+/+) or deficient of IL4i1 (IL-4i1-/- ) backcrossed to BALB/c genetic background were used in this study. For induction of allergic asthma, a high dose (100µg/per mouse) of house dust mite (HDM) was used in sensitizing mice intratracheally at day 0 and challenged at day 7 to 11 intranasally under anaesthesia. To assess the development of asthma features, we measured lung function on day 14 and collected blood for ELISAs, mediastinal lymph nodes, and lung tissues for FACS and RNA. For induction of AD, a skin irritant vitamin D3 analog (MC903) was used to topically sensitize shaved mice (IL-4i1+/+ or IL-4i1-/- ) for 9 consecutive days. We assessed disease score and skin inflammation at day 10 and collected blood, inguinal lymph nodes, and skin for ELISAs, FACS, RNA, and histology analysis. In both disease models, we saw a significant reduction in total IgE in IL-4i1- deficient mice compared to IL-4i1+/+ littermate controls. A significant upregulation of Th2 cytokines and increased eosinophilia was seen in IL-4i1 deficient mice in the allergic asthma model with no changes in airway hyperresponsiveness. In AD model, we observed a protective effect in the absence of IL-4i1, which was demonstrated by no changes in body weight a reduced skin epidermal thickness, and reduced systemic type 2 cytokines, TSLP, IL-5, and IL-13 producing CD8 T cells. Furthermore, type 2 alarmin, TSLP was reduced at disease site. These results suggest a dichotomy of IL4i1 in regulation of type 2 immune responses depending on disease site. This data further suggests that IL4i1 may be a potential target for therapy against these diseases. Studies are currently underway to understand how IL-4i1 is induced and how it regulates downstream effector molecules and how these target molecules can be inhibited.